Determining the effect of land consolidation on agricultural production using a novel assessment framework. (6th January 2020) - Hong, Changqiao; Jin, Xiaobin; Fan, Yeting; Xiang, Xiaomin; Cao, Shuai; Chen, Changchun; Zheng, Guang; Zhou, Yinkang
Abstract: Land consolidation (LC) is regarded as a useful tool to improve agricultural production. Measuring the effect of LC on agricultural production (ELCAP ) is helpful for the planning of LC activities. In the past, it is difficult to measure ELCAP at regional level due to the lack of field observation, the change of crop planting structure, and high cost of sample collection. Satellite data have large coverage and high spatiotemporal resolution for vegetation observation, which can provide a new idea for estimating ELCAP at regional level. This study aims to build a novel assessment framework to quantitatively investigate ELCAP by developing several satellite‐based metrics. In addition, this study also explored the characteristics of ELCAP using the method of spatial autocorrelation and the geographical detector method in 1, 281 LC areas in China. Our results show that agricultural productivity in more than 90% of total LC areas shows an increasing trend during 2001–2016. LC could play the positive but limited effects on agricultural production, and its productivity‐boosting effect (64.87% of total LC areas) is greater than its stability‐improving effect (46.53% of total LC areas). The spatial agglomeration of ELCAP is weak (Moran's I < 0.06), which may be resulted from the differences in field conditions and natural‐social–economic situations across LC areas. The interaction between several factors has a greater effect on the ELCAP than each of these factors. Methodology in this study provides a new and useful framework for evaluating ELCAP, and results can be used to guide the planning of LC activities.